Aplikasi Pembagian Harta Warisan Menurut Hukum Islam Berbasis Android - Purnomo, Dwi; , Dr. Heru Supriyono, S. Mc; , Drs. Ramelan M. Ag (2016)
Android is an open operating system with complete library and smartphone with android operating system is relatively more cheap than another smartphone. This is triggers for various parties to develop android application, as well as with this faraid apllication. Faraid derived from the Arabic which means "division", or more explicit defined a science which describes procedures for division of property from someone who has died with the divisions that have been determined to be distributed to who rightfully deserve it. In everyday life, heritage is often a complicated issue and often a source of dissension, for that's require a fair inheritance law. The science that handle aboutt inheritance is a science that Allah is deign to explain the distribution explicitly. The importance of faraid science for muslims and the development trend of mobile technology today is so fast, therefore requires a calculation of inheritance application based faraid law which can be used without the limited space and time with expanding into mobile appliation. For the research methodology this software uses waterfall method, whereas for data modeling using object-oriented methods that's is Unified Modeling Language (UML) to describe the model of analysis and system design to be created. Based on the result of testing the functionality, application which is used for help calculate the distributionn of the inheritance based faraid law successfully developed and insya'allah give right result. Keyword : Mobile Application, Android, Faraid, Muslim